Biomechanical effectiveness of controlled ankle motion boots: A systematic review and narrative synthesis - Mason L. Stolycia; David E. Lunn; Will Stanier; Josh Walker; Richard A. Wilkins (Journal of Foot and Ankle Research, 2024)
Abstract Introduction Controlled ankle motion (CAM) boots are a below‐knee orthotic device prescribed for the management of foot and ankle injuries to reduce ankle range of motion (RoM) and offload the foot and ankle whilst allowing continued ambulation during recovery. There is a lack of clarity within the current literature surrounding the biomechanical understanding and effectiveness of CAM boots. Aims To summarise the biomechanical effects of CAM boot wear as an orthotic for restricting ankle RoM and offloading the foot. Methods A systematic literature review was conducted in accordance with the PRISMA 2020 guidelines. All papers were independently screened by two authors for inclusion. Methodological quality was appraised using Joanna Briggs Critical Appraisal checklists. A narrative synthesis of all eligible papers was produced. Results Thirteen studies involving 197 participants (113 male and 84 female) were included. All studies were quasi‐randomised and employed a within‐study design, of which 12 studies included a control group and a range of CAM boots were investigated. CAM boots can be seen to restrict ankle RoM, however, neighboring joints such as the knee and hip do have kinetic and kinematic compensatory alterations. Plantar pressure of the forefoot is effectively redistributed to the hindfoot by CAM boots. Conclusion The compensatory mechanisms at the hip and knee joint during CAM boot wear could explain the secondary site pain often reported in patients, specifically at the ipsilateral knee and contralateral hip. Although CAM boots can be used to restrict ankle motion, this review has highlighted a lack of in‐boot kinematic analyses during CAM boot use, where tracking markers are placed on the anatomical structure rather than on the boot, or through video fluoroscopy, urging the need for a more robust methodological approach to achieve this. There is a need for studies to assess the biomechanical alterations caused by CAM boots in populations living with foot and ankle pathologies. Future research, adopting a longitudinal study design, is required to fully understand the effectiveness of CAM boots for rehabilitation.